PERBANDINGAN JUMLAH WISATAWAN ASING DAN DOMESTIK DI KABUPATEN BANYUMAS - Seftina Diyah Miasary; Novita Eka Chandra (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2017)
Tourism is part of the tax and income of a region. Based on data from the Central Bureau of Statistics Banyumas district, tourism in Banyumas district is very rapid. Banyumas district strategic location factor, many foreign and domestic tourists who visit to enjoy the tourist attractions and even the existing culinary. The study used data taken from the Central Bureau of Statistics Banyumas district in 2002 until 2014. After doing research on tourists in Banyumas district obtained that there are differences in the number of foreign and domestic tourists, and there is no difference in average length of stay foreign and domestic tourists in the district of Banyumas .